Poster 247: Muscle ERRγ Overexpression Mitigates the Muscle Atrophy after ACL injury. Issue 7 (30th July 2022) - Huard, Johnny; Guo, Ping; Huard, Matthieu; Gao, Xueqin; Narkar, Vihang A.; Tashman, Scott; Huard, Johnny; Lu, Aiping
Objectives: Anterior cruciate ligament (ACL) reconstruction is the 6th most common orthopedic procedure performed in the United States (1, 2). There is substantial evidence to suggest that muscle weakness significantly contributes to adverse outcomes after ACL injury/reconstruction (3). Despite efforts to improve rehabilitation methods, there are currently no effective strategies for restoring pre-injury muscle strength in ACL-injured limbs. Our team has identified that estrogen-related receptor gamma (ERRγ) is a crucial regulator of paracrine angiogenesis in the skeletal muscle (4). Selective over-expression of ERRγ in the skeletal muscle [ERRGO mice] activates a robust paracrine angiogenic gene program involving myofibrillar induction and secretion of a battery of angiogenic factors resulting in muscle vascularization (4). To determine if muscle ERRγ-driven angiogenesis can mitigate muscle atrophy after ACL injury, we performed ACL injury on the ERRGO mice, as well as age-matched wild-type (WT) littermate control mice. In this model, we found that ERRGO mice with muscle ERRγ overexpression significantly mitigated muscle atrophy compared to WT control mice 4 weeks after ACL injury. This finding strongly suggests that muscle-specific ERRγ activation may reduce muscle atrophy after ACL injury as a consequence of increased muscle angiogenesis. This preventive effect is potentially linked to developing a therapeutic approach to reverse these muscle changes after ACL surgery. Methods:Animals: 12 weeks old male and female ERRGO and WT mice obtained from Dr. Narkar's laboratory were used for this study. The ACL injury was conducted as previously described (5). We performed ACL injury on the right leg, and the left leg was used as non-injured control. The mice were euthanized four weeks after injury. The muscle tissues were harvested, the gastrocnemius muscle (GM) mass was weighted, flash-frozen in liquid nitrogen-cooled 2-methylbutane, and cryo-sectioned.H&E staining was performed on 10 µm cryosections from GM according to the manufacturer's instructions. Immunohistochemical staining: The muscle sections were fixed with 4% paraformaldehyde. A Mouse on Mouse kit (Vector) was used for anti-muscle RING-finger protein-1 (MuRF1, marker for muscle atrophy) staining according to the manufacturer's protocol.Statistical analysis: All results are presented as mean ± standard deviation (SD). Means from ACL injured and non-injured of WT and ERRGO mice were compared using Student's t-test. Differences were considered statistically significant when the P-value was < 0.05. Results: We performed the following experiments to determine if ERRγ overexpression in the muscle can prevent muscle weakness after ACL injury. The ACLs on the right leg of ERRGO and WT mice were excised. 4 weeks after injury, the mice were sacrificed, and muscle tissues were collected for histology analysis. First, we observed that muscles in the hindlimbs of WT mice were atropied, as expected, after ACL injury compared to the muscles in the non-injured hindlimb (Fig.1A ). Strikingly, after ACL injury, the hindlimb muscles in ERRGO mice were resiliant to atrophy (Fig.1A ). Quantitatively, we found that the gastrocnemius muscles weights were significantly reduced in WT mice after ACL injury compared to the GM weights from the non-injured leg. However, this ACL injury-induced reduction in gastrocnemius weight was not observed in ERRGO mice after ACL injury (Fig.1 B ). The myofiber cross-sectional area (CSA) was measured based on the H&E staining on the GM muscle of ERRGO and WT mice to evaluate the muscle atrophy further. We found that the CSA of muscle fibers in WT mice was significantly smaller after ACL injury than in the non-injured control muscle (Fig. 2A, 2C, P<0.05 ). The average size of muscle fibers was not significantly decreased in the muscle of ERRGO mice after ACL injury compared to non-injured muscle. (Fig. 2A, 2C, P>0.05 ). Since MuRF1 is a biomarker of myofiber atrophy (6), we evaluated the MuRF1 expression in muscle sections by immunostaining. The result showed an increase in MuRF1 expression in the WT muscle compared to ERRGO muscle after ACL injury (Fig. 2B ). Together, those results demonstrated that muscle-specific ERRγ activation mitigates muscle atrophy after ACL injury. Conclusions: Skeletal muscle is adversely affected by the ACL injury, and post-reconstruction recovery is limited by muscle weakness. It has been reported that ERRγ expression in the skeletal muscle directly correlates with vascular density, and ERRγ is highly expressed in well-vascularized muscle beds (4). Based on our preliminary data, we observed that the ERRGO mice with muscle-specific ERRγ activation have the capacity to mitigate the muscle atrophy after ACL injury. As we know, exercise induces muscle angiogenesis, and regular physical activity has been considered a therapeutic modality for preventing aging-related muscle wasting. Although exercise is the primary method for alleviating muscle weakness, many patients cannot achieve the exercise intensity that is necessary to prevent or reverse muscle atrophy. Drugs targeting ERRγ will likely be safe as ERRγ belongs to the nuclear receptor superfamily, which are excellent 'druggable' targets with unique ligand-binding pockets that facilitate selective and specific drug design. Future studies will investigate the beneficial effects of ERRγ overexpression in ERRGO mice on muscle atrophy after ACL injury at different time points and determine if muscle-specific activation of ERRγ can mitigate age-related muscle progenitor cells dysfunction and offset the infiltration and activation of FAPs and senescent cells after ACL injury